Developing the Evaluative Model for Cultural Policy Making Process based on Qualitative Study of Cultural Documents of Islamic Republic of Iran - Hossein Gorjipour; Vahid khashei; Alireza Eslambolchi; Ali Asghari Sarem (مدیریت دولتی, 2019)
Objective: Evaluation of cultural policy- making process in Islamic Republic of Iran which is identified based on cultural identity- needs a native pattern according to the religious culture of the Iranian community,because transmission of non-native evaluative patterns of cultural policy cannot be the gateway to this field.This research aims at identifying and forming utility indexes on each stage of the cultural policy-making process in Islamic Republic of Iran. Methods: Research is conducted based on qualitative analysis of the three documents, cultural engineering map of the country, culture-related chapter of “the development prospects (1404)” and “Islamization of the country's universities”, using theme analysis as a process for analyzing text data. Results: Utility indexes on the cultural policy-making process are as follows: The understanding and realization of the problem stage includingawareness and cognition, social growth, identity and deepening of the principles and religious education; The formulation of solution stage including efficiency, innovation, need-based and rational scientific issues; The legitimation stage including persuading and legal support; The implementation stage including synchronizing the time and place, structuring, soft and hard supplying and succeeding in legitimacy; and The evaluation stage including multi-level monitoring, continuous monitoring and intelligent monitoring. Conclusion: Evaluative model in the cultural policy-making process helps policy makers and enforcers and stakeholders, at the first step, to prevent potential damage in decisions and cultural activities. In the next step, if it fails to reach cultural goals, by referring to the proposed model, they could identify the obstacles and problems and tend to solve them.